Active Platinum Nanoparticles as a Bifunctional Promoter for Lithium−Sulfur Batteries. Issue 10 (14th July 2017) - Lin, Zejing; Li, Xia; Huang, Wenlong; Zhu, Xi; Wang, Yun; Shan, Zhongqiang
Abstract: As a widely used electrocatalyst in fuel cells, metallic platinum has achieved great success in terms of kinetic promotion. Still plagued by a familiar problem, owing to the sluggish kinetics of irreversible Li2 S2 /Li2 S species deposition, lithium−sulfur batteries with high theoretical energy are far from being realized. Inspired by the similarity between oxygen and sulfur, being in the same group, commercially available Pt/C was investigated here to explore the possible effect on the sulfur cathode. The electrochemical tests show that the electrode with 2 wt% Pt added delivers a 61 % enhancement in the discharging specific capacity compared to the control electrode after 200 cycles at 0.5 C, along with an average coulombic efficiency of 98.3 %. It is proven that these beneficial results can be attributed to the favorable capability of polysulfide immobilization and effective inhibition of self‐discharging behavior. The ex situ XPS analysis and the increased exchange current density further reveal that the involved platinum nanoparticles could not only function as a static chemical absorber for polysulfide species, but, more importantly, to promote the redox kinetic effectively as an electrochemical catalyst. The positive effect of utilizing commercial Pt/C materials directly on sulfur cathodes is of great significance in developing sulfur cathodes for Li/S batteries. Abstract : Old dogs, new tricks : The commercially available Pt/C fuel cell catalyst is introduced into the lithium−sulfur system. The shuttle effect of soluble polysulfide as well as the irreversible deposition of the Li2 S2 /Li2 S can be effectively mitigated, owing to the strong chemical interaction and promoted electrochemical conversion provided by the Pt nanoparticles.